2008
DOI: 10.3113/fai.2008.0049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a Novel FiberWire-Button Construct versus Metallic Screw Fixation in a Syndesmotic Injury Model

Abstract: The FiberWire-button implant may not maintain adequate ankle syndesmotic reduction in the immediate post-operative period relative to a metallic screw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 35 publications
1
84
0
Order By: Relevance
“…The more recent development is the Endobutton fixation and its use is rapidly increasing; potentially, this technique has the following advantages: allows physiologic micromotion at the syndesmosis and thus an earlier return to weightbearing was possible, lessens the risk of hardware pain and the implant removal will not be necessary, without the risk of screw breakage and subsequent recurrent syndesmotic diastasis [15,[23][24][25]. However, this method still has some defects such as the suture loop may relax under weightbearing conditions, local irritation, osteolysis of the bone and subsidence of the device into the bone (as was occasionally observed), and its relatively high cost and complexity [17,26]. The bionic fixation construct we described in the present study was developed with the goal of more accurately recreating the native anatomy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The more recent development is the Endobutton fixation and its use is rapidly increasing; potentially, this technique has the following advantages: allows physiologic micromotion at the syndesmosis and thus an earlier return to weightbearing was possible, lessens the risk of hardware pain and the implant removal will not be necessary, without the risk of screw breakage and subsequent recurrent syndesmotic diastasis [15,[23][24][25]. However, this method still has some defects such as the suture loop may relax under weightbearing conditions, local irritation, osteolysis of the bone and subsidence of the device into the bone (as was occasionally observed), and its relatively high cost and complexity [17,26]. The bionic fixation construct we described in the present study was developed with the goal of more accurately recreating the native anatomy.…”
Section: Discussionmentioning
confidence: 89%
“…More recently, flexible fixation using the suture button device has been applied, which allows physiologic motion in the tibiofibular joint and, meanwhile, maintains the reduction of the ankle [14][15][16]. However, this method still has some drawbacks such as the suture between buttons can gradually relax under weightbearing conditions [17], and it has a relatively high cost and complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate fixation and foreign-body reactions from the suture-button placement have been reported. 10,16,25,32 Fracture of the index metacarpal has also been reported following SBS. 15,36 Since those reports, the Arthrex secondgeneration Mini TightRope kit includes a 1.1-mm guidewire to drill the metacarpal instead of the 2.7-mm drill used in the earlier systems.…”
Section: Discussionmentioning
confidence: 99%
“…[130][131][132][133][134][135][136][137][138][139][140][141][142][143][144] A hole is drilled through the fibula and tibia, and then a suture is passed through and secured on both ends via a metallic button. Systematic reviews of low levels of clinical evidence have demonstrated similar functional outcomes, with quicker return to work and less frequent need for implant removal.…”
Section: Dynamic Fixationmentioning
confidence: 99%